Dampak dan Strategi untuk Mengatasi Kecemasan Berbicara dalam Pembelajaran Bahasa Inggris sebagai Bahasa Ke-2 (ESL) dan Asing (EFL) - Thomas Joko Priyo Sembodo (JLA (Jurnal Lingua Applicata), 2018)
This paper aims at addressing the issue of speaking anxiety in ESL/EFL learning. This study of literature is believed to be significant as it can give insights into ESL/EFL anxiety and how it can be coped. In doing so, this paper starts with the description of the nature of language anxiety in ESL/EFL learning particularly speaking anxiety, its theoretical overview, causes of such an anxiety, and its effects on ESL/EFL learning. Furthermore, there is a review of studies on strategies used to cope with language and speaking anxiety in ESL/EFL learning or classrooms. These coping strategies can be classified into two categories, namely 1) self-employed strategies employed by anxious learners consisting of five strategies--in which two are inapplicable, and 2) employed by teachers, which consists of three strategies. Those strategies are able to help overcome the learner’s anxiety, leading to the more successful ESL/EFL learning. In addition, in ESL/EFL classrooms teachers play a key role in relieving anxiety experienced by their students. In conclusion, speaking anxiety can have debilitating impacts on learners experiencing it. However, this problem can be overcome with strategies employed by learners and their teachers.